The changing face of innovation is it shifting to Asia? - Ramakrishna, Seeram (World Scientific Pub. Co., 2012)
This book provides a brief overview of the recent trends in innovations. Early inventions/innovations that began in Asia (i.e., compass, paper, gunpowder and printing) spread to the Atlantic (Europe and USA) by land and sea routes. However, with population growth, economic expansion, availability of skilled researchers and lower cost of research in Asia Pacific, there has been a shift in innovation activities in this region. There has been a discernable trend of innovation (R&D) in countries like Japan, Korea, China, India and Singapore. This book attempts to create awareness of this trend and hopes to motivate business leaders and policy makers to take advantage of this shifting trend, as well as to encourage more global collaboration in innovations to face societal challenges in the 21st century
Keywords: Technology and state / Asia; Appropriate technology / Asia; Technological innovations / Asia; Economic development / Asia